2023
DOI: 10.1002/bse.3602
|View full text |Cite
|
Sign up to set email alerts
|

From green hype to green habits: Understanding the factors that influence young consumers' green purchasing decisions

João M. Lopes,
Micaela Pinho,
Sofia Gomes

Abstract: It is believed that environmental causes will grow in fervor with members of Gen Z. This study explores the main factors of green marketing affecting young Portuguese green purchasing decisions and the relationship between them. An online questionnaire was used to collect data from 708 young Portuguese consumers of eco‐friendly products. The quantitative analysis was performed using the partial least square (PLS) method. We found that the marketing factors of green willingness to purchase, green awareness of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…They are considered the most technologically savvy generation, and smartphone represents the most commonly used technological device among this group (Ayuni, 2019). Gen-Z, being considered more ethical in their consumption (Francis & Hoefel, 2018), are thus more likely to incline towards the consumption of green products (Lopes et al, 2023). In a study by Noor et al (2017), it was concluded that Gen-Z's attitude towards green activities, subjective norms, perceived green knowledge, and social visibility significantly affected their green purchase decision.…”
mentioning
confidence: 99%
“…They are considered the most technologically savvy generation, and smartphone represents the most commonly used technological device among this group (Ayuni, 2019). Gen-Z, being considered more ethical in their consumption (Francis & Hoefel, 2018), are thus more likely to incline towards the consumption of green products (Lopes et al, 2023). In a study by Noor et al (2017), it was concluded that Gen-Z's attitude towards green activities, subjective norms, perceived green knowledge, and social visibility significantly affected their green purchase decision.…”
mentioning
confidence: 99%